Complete genome sequence analysis of the fish pathogen Flavobacterium columnare provides insights into antibiotic resistance and pathogenicity related genes. (October 2017) - Zhang, Yulei; Zhao, Lijuan; Chen, Wenjie; Huang, Yunmao; Yang, Ling; Sarathbabu, V.; Wu, Zaohe; Li, Jun; Nie, Pin; Lin, Li
Abstract: We analyzed here the complete genome sequences of a highly virulent Flavobacterium columnare Pf1 strain isolated in our laboratory. The complete genome consists of a 3, 171, 081 bp circular DNA with 2784 predicted protein-coding genes. Among these, 286 genes were predicted as antibiotic resistance genes, including 32 RND-type efflux pump related genes which were associated with the export of aminoglycosides, indicating inducible aminoglycosides resistances in F. columnare . On the other hand, 328 genes were predicted as pathogenicity related genes which could be classified as virulence factors, gliding motility proteins, adhesins, and many putative secreted proteases. These genes were probably involved in the colonization, invasion and destruction of fish tissues during the infection of F. columnare . Apparently, our obtained complete genome sequences provide the basis for the explanation of the interactions between the F. columnare and the infected fish. The predicted antibiotic resistance and pathogenicity related genes will shed a new light on the development of more efficient preventional strategies against the infection of F. columnare, which is a major worldwide fish pathogen. Highlights: A complete genome map of F. columnare was constructed. 286 antibiotic resistance genes and 328 pathogenicity related genes were identified. Inducible aminoglycosides resistances may occur in F. columnare. Gene analysis demonstrated a strong virulent strain of Pf1 during infection.